2013
DOI: 10.1371/journal.pntd.0002237
|View full text |Cite
|
Sign up to set email alerts
|

Aedes Mosquito Saliva Modulates Rift Valley Fever Virus Pathogenicity

Abstract: BackgroundRift Valley fever (RVF) is a severe mosquito-borne disease affecting humans and domestic ruminants. Mosquito saliva contains compounds that counteract the hemostatic, inflammatory, and immune responses of the host. Modulation of these defensive responses may facilitate virus infection. Indeed, Aedes mosquito saliva played a crucial role in the vector's capacity to effectively transfer arboviruses such as the Cache Valley and West Nile viruses. The role of mosquito saliva in the transmission of Rift V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 39 publications
1
69
0
Order By: Relevance
“…We published evidence of this dilution in previous studies, which showed that the amount of WNV in artificially collected mosquito saliva is 100-fold lower than the amount of virus inoculated by a mosquito into a live host (19). For these reasons, artificially collected mosquito saliva is infrequently used for in vivo studies, and SGE has been used as a substitute for mosquito saliva in numerous experimental systems (11,16,20,(27)(28)(29)(30)(31)(32)(33)(34)(35). We thus used SGE, which contains secreted salivary factors representative of those obtained by both blood and sugar feeding and which can be produced in sufficient quantities with minimal manipulations that could reduce or eliminate functional activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We published evidence of this dilution in previous studies, which showed that the amount of WNV in artificially collected mosquito saliva is 100-fold lower than the amount of virus inoculated by a mosquito into a live host (19). For these reasons, artificially collected mosquito saliva is infrequently used for in vivo studies, and SGE has been used as a substitute for mosquito saliva in numerous experimental systems (11,16,20,(27)(28)(29)(30)(31)(32)(33)(34)(35). We thus used SGE, which contains secreted salivary factors representative of those obtained by both blood and sugar feeding and which can be produced in sufficient quantities with minimal manipulations that could reduce or eliminate functional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Deer and chipmunks infected with La Crosse virus by infected Aedes mosquitoes have higher levels of viremia than animals inoculated with virus by needle (10). Mice inoculated with Rift Valley Fever virus and salivary gland extract (SGE) or with Rift Valley Fever virus by infected Aedes aegypti mosquitoes have increased levels of virus in the blood, liver, and brain and enhanced mortality (11). Mice inoculated with dengue virus (DENV) in areas of A. aegypti probing (12,13) or by DENVinfected A. aegypti mosquitoes (13) have higher levels of viremia than mice inoculated by needle.…”
mentioning
confidence: 99%
“…Using in vitro saliva collections it is calculated that mosquitoes inject around 50 p.f.u. ml À1 RVFV with each bite [48,49] although analysis of West Nile virus (WNV; Flavivirus), suggests these methods underestimate titres and vary between species [50].…”
Section: Introductionmentioning
confidence: 99%
“…Infection by these arboviruses through mosquito saliva results in an increase in virus transmission, host susceptibility, viremia, disease progression and mortality [136][137][138][139][140][141][142][143][144]. In the case of arbo-bunyaviruses, the infection of mice is potentiated by the co-injection of mosquito saliva with RVFV or Cache Valley virus, an orthobunyavirus [145,146]. Similarly, co-injection with LACV potentiates infection of white-tailed deer and chipmunks [147].…”
Section: Release Of Viruses Into the Host Dermis By Infected Arthropodsmentioning
confidence: 99%